Nonspecific Symptoms in a Rare Case of Urethral Adenocarcinoma in a 58-Year-Old Female. (23rd May 2018) - Gustafson, Line Winther; Christiansen, Anne Gamst; Majeed, Huda; Humaidan, Peter
Abstract : Cancer of the urethra is very rare with an age-adjusted incidence of only 0.6 per million women in Europe. The etiology is multifactorial and the incidence increases with age, with the highest rates in patients 75 years or older. We herein describe a 58-year-old woman referred to our unit due to pollakisuria and repeated lower urinary tract infections. The gynecological examination revealed a suspect area in the anterior wall of vagina. Subsequently, ultrasound examination, MRI, and PET-CT scan followed by vaginal biopsies revealed a urethral adenocarcinoma.